Greenways in Landscape Planning – Case Study: Municipality of Subotica - Klara Marijanušić; Saša Orlović; Aleksandar Kurjakov; Lazar Pavlović; Maja Manojlović (Fábos Conference on Landscape and Greenway Planning, 2016)
Municipality of Subotica is located at the northern part of the Vojvodina Province and Republic of Serbia, along the Hungarian border. The natural heritage of the Vojvodina Province (North part of Serbia) is extraordinary diverse with important ecosystem diversity. In the Vojvodina province there are extra natural and landscape areas specific for the South – East Europe as Deliblato sands (the biggest sand area in the Europe), hilly areas of Fruška Gora and Vršački breg. Also, the rivers Danube, Sava, Tisa, Begej, Tamiš and their floodplain zones (Apatinski rit, Monoštorski rit, Koviljski rit, Obedska bara, Carska bara, etc.), the steps zones in Middle and North Banat, loess area along the Tisa and Danube rivers (Titelski breg, Slanka men, Surduk). The protected areas on saline soils (Slano kopovo, Rusanda and Okanj) are also very important. The protected area network consists of about 200 spatial entities, which cover 5.5% of the total Province area (Orlović et al, 2005.). According to the Law of natural protection in municipality of Subotica there are four zones under special protection (Figure 1). Ludaš lake and Selevenj heath are strict nature reserves with total area of 846.33 ha (Official Gazette RS, 2006) and 677.04 ha (Official gazette RS, 1997), respectively. The areas are important due to rich diversity of lowland habitat types, as well as extremely high levels of floral diversity with a significant number of endangered species of authentic Pannonian flora and fauna. Ludaš lake also has an international significance (Ramsar wetland) because it represents a meeting place and place for rest of migratory bird species. Subotica sands is ranked as land of exceptional feature (5370 ha) which is characterized by unique environmental conditions, in terms of sand geological ground, variety of soil and special regime of ground water (Official Gazzete RS, 2004). The fourth area under special protection is nature park Palić with total area of 712.3 ha. Besides natural resources and the rich biodiversity, this area is also important for tourism development due to the numerous cultural value: the archaeological sites dating from the Stone Age and the Middle Age as well as examples of architecture in Art Nouveau style. There is also a large number of ethno houses showing the life, traditions and crafts typical for the northern Serbia. Construction of an international highway that passes through the region caused an additional pressure on the ecosystem of these areas. According to Ahern (1995): „greenways are networks of land containing linear elements that are planned, designed and managed for multiple purposes including ecological, recreational, cultural, aesthetic, or other purposes compatible with the concept of sustainable land use“. Ecological function of greenway is important, linking isolated areas and helping to improve local biodiversity in several ways: by allowing individual animals access to a larger area of habitat; facilitating seasonal migration and genetic exchange with other local populations of the same species; and offering opportunities for individuals to move away from a habitat that is degrading or from an area that is under threat (Benett and Mulongoy, 2006). Landscape connectivity is not only important because environment protection, but it also has social and cultural goals (Ahern, 1995). Greenways can develope activities, such as nature tourism, environmental education that will promote landscape sustainability and stimulate social, economic and ecological dynamics (Pena et al., 2010).
Keywords: greemways; landscape planning; subotica; serbia